2021
DOI: 10.3389/fendo.2021.666315
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Based on Clinical and Ultrasound Characteristics to Predict Central Lymph Node Metastasis of Papillary Thyroid Carcinoma

Abstract: BackgroundThe status of lymph nodes in the central compartment is crucial to determining the surgical strategies for papillary thyroid carcinoma (PTC). We aimed to develop a nomogram for predicting central lymph node metastasis (CLNM).MethodsA total of 886 PTC patients who underwent total thyroidectomy or lobectomy with central neck dissection (CND) from July 2019 to June 2020 were retrospectively retrieved. Clinical and ultrasound features were collected. Univariate and multivariate analysis were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
3
28
1
1
Order By: Relevance
“…In previous studies (32,33), serum thyroglobulin could generally be assessed by lymph node puncture before surgery to determine the status of lymph node metastasis or tumor recurrence after surgery. Besides, previous studies (27,28) have shown that male patients are more likely to have CLNM in PTC, which was reflected in patients older than 45 years, but this trend was not obvious in younger patients. It is well known that differences in sex hormones are more common in younger patients, so the above finding is intriguing.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In previous studies (32,33), serum thyroglobulin could generally be assessed by lymph node puncture before surgery to determine the status of lymph node metastasis or tumor recurrence after surgery. Besides, previous studies (27,28) have shown that male patients are more likely to have CLNM in PTC, which was reflected in patients older than 45 years, but this trend was not obvious in younger patients. It is well known that differences in sex hormones are more common in younger patients, so the above finding is intriguing.…”
Section: Discussionmentioning
confidence: 84%
“…There are other studies on proteomics and fibronectin expression in CLNM (24,25). In almost all studies (26)(27)(28), age, tumor size, gender, multifocality and extrathyroidal extension were considered risk factors for CLNM, but all these reports were based on the overall population without age stratification. It is well-known that age is an important factor affecting the biological behavior of the thyroid, and an important prognostic indicator in thyroid cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…After that, a nomogram was constructed to screen out the relatively high-risk patients in clinical practice; and this population might need extended resection and lymphadenectomy. Nomograms are widely used to predict prognosis, skip metastasis, and central lymph node metastasis in thyroid carcinoma [ 59 61 ]. To give clinicians a practical tool for individualized prognosis prediction, we constructed a nomogram based on the independent factors in the multivariate Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researchers made an effort to study the association between US characteristics of PTCs and CLNM, nding that it may be a promising strategy to predict CLNM before surgery to avoid unnecessary pCND [20,21]. Previous studies have shown that the most important contributing factors to CLNM including patient age, male, multifocality, tumor size and location, margin, microcalci cation, ETE and concomitant HT [14,22,23]. In this study, some conventional US characteristics of PTCs can be predictors of CLNM, including larger maximum size, tall than wide, contact capsule and US reported ACLN.…”
Section: Discussionmentioning
confidence: 99%
“…It was recognized that there remains an existing need for improved CLNM prediction performance. Available studies have established the prediction model by regression algorithm and nomogram, making it possible to forecast CLNM risk in clinical application [14][15][16]. Machine learning (ML) algorithm has been widely used in image diagnosis over the last few years.…”
Section: Introductionmentioning
confidence: 99%